The Existentialist Manifestations in the Poetry of Badr Shakir al-Sayyaab - Khezri, Ali (Journal of Human Sciences, 2021)
The school of existentialism is a philosophical school that speaks of humanity and its originality, which is based on the primacy of being on nature, and considers everything owned by human being. Philosophers like Martin Heidegger, Jean-Paul Sartre, etc founded this philosophical school that revolves around the human axis and overshadowed western literature. The ideas of this philosophical school also found their way into the contemporary Arabic literature and many poets, including the contemporary Iraqi poet Badr Shakir al-Sayyab, influenced by this school, have put man at the heart of their poems. In this article, we are going to analyze the effect of this philosophical school on his poems by analyzing the school of existentialism and studying the poems of Sayyab with the following themes: human, life, mortality, freedom, commitment, etc. From the point of view of the poet, man in this material world is strange and alien, Sayyab is trying to release man of his confinements in order to attain the true meaning of freedom. The poet does not consider death as the end of the human life; instead he mentions it as a point for the beginning of another life for the surrounding people. He regards death as a vitalizing and life-giving stream which contradicts the view of existentialism..